Effect of Flat-Knitted Medical Compression Stockings on Venous Malformations - Li, Yi; Muekke, Antje; Rother, Ulrich; Janka, Rolf Matthias; Uder, Michael; Lang, Werner; Heiß, Rafael (Journal of Clinical Medicine, 2023)
Venous malformations are one of the most common vascular anomalies. Our study aimed to investigate the effect of medical compression stockings of class I and II on the volume of venous malformations. Patients with venous malformations on upper or lower extremities were enrolled. They wore flat-knitted medical compression stockings of class I and II in a randomized order for four weeks each. Magnetic resonance imaging (MRI) and perometry were performed with and without wearing compression stockings. The 12-Item Short Form Survey (SF-12) questionnaire was performed before and after wearing compression stockings for four weeks each. A total of 18 patients completed the evaluations. Both compression classes showed a significant reduction of the volume of the venous malformations in the lesion itself based on MRI in comparison with baseline (both p < 0.001). Measurements taken with perometry did not reveal a significant difference in comparison to baseline (p = 0.09 and p = 0.22). The results of the SF-12 questionnaire demonstrated no significant differences before and after wearing the compression stockings of class I or class II for four weeks or between the two classes of compression therapy. Our results indicate that wearing medical compression stockings of both class I and class II significantly reduces the volume of venous malformation, without compromising the quality of life, while the effect of class II compression stockings on volume reduction was significantly better than that of class I.
CRIS-Team Scopus Importer:2023-04-28
Keywords: compression stockings; magnetic resonance imaging; perometry; quality of life; T2-weighted imaging; venous malformation